2021
DOI: 10.30738/indomath.v4i1.9339
|View full text |Cite
|
Sign up to set email alerts
|

Depicting Epistemological Obstacles in Understanding the Concept of Sequence and Series

Abstract: This study aimed to discover epistemological obstacle on secondary students to solve sequence and series problems based on three indicators, there are a conceptual obstacle, procedural obstacle, and operational technique obstacle. This study was descriptive with qualitative research approaches. Data were collected with the test and interview method. The subjects in this study are students of SMP Negeri 86 Jakarta class VIII based on the errors seen from the diagnostic tests that had been tested. The analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
2
0
4
Order By: Relevance
“…This indicates that students have learning obstacles in sequence and series material. Researchers' findings show that many studies have revealed similar things (Hardiyanti, 2016;Maarif et al, 2021;Rachma & Rosjanuardi, 2021). The difficulties experienced by students are caused by errors in delivering the material, giving rise to misconceptions in acquiring knowledge (Tümay, 2016).…”
Section: Comparison Of Bi and Bmmentioning
confidence: 94%
See 1 more Smart Citation
“…This indicates that students have learning obstacles in sequence and series material. Researchers' findings show that many studies have revealed similar things (Hardiyanti, 2016;Maarif et al, 2021;Rachma & Rosjanuardi, 2021). The difficulties experienced by students are caused by errors in delivering the material, giving rise to misconceptions in acquiring knowledge (Tümay, 2016).…”
Section: Comparison Of Bi and Bmmentioning
confidence: 94%
“…This topic is important because it is often encountered in everyday life (Putri et al, 2023;Rachma & Rosjanuardi, 2021), such as sales, purchasing activities, and calculating the proceeds from the sale of goods (Putri et al, 2023). However, previous research reveals that students' abilities in this topic are still low (Maarif et al, 2021;Rachma & Rosjanuardi, 2021). For this reason, the results of this textbook analysis have the potential to provide a broader and deeper picture (Gracin, 2018).…”
Section: Introductionmentioning
confidence: 91%
“…Hambatan epistimologi muncul akibat keterbatasan pengetahuan siswa terhadap konteks tertentu karena tidak memperoleh informasi secara utuh yang akan berakibat pada kesulitan siswa dalam mencari hubungan serta dalam keterkaitan konsep [9]. Hambatan epistimologi berhubungan erat dengan kesalahan dan kesulitan yang terjadi pada objek kajian abstrak matematika, objek matematika yang dimaksud diantaranya berupa konsep, fakta, serta prinsip [3].…”
Section: Pendahuluanunclassified
“…Hambatan epistimologi berhubungan erat dengan kesalahan dan kesulitan yang terjadi pada objek kajian abstrak matematika, objek matematika yang dimaksud diantaranya berupa konsep, fakta, serta prinsip [3]. The indicators in analyzing the data use the indicators of epistimological barries, namely conceptual barries, procedural barries and operational of technical barries [9]. Indikator dalam hambatan epistimologi berupa tiga hal, yaitu hambatan konseptual, hambatan prosedural dan hambatan teknik operasional.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation